Persepsi Birokrasi dan Pemangku Kepentingan terhadap Transparansi Anggaran di Pemerintahan Kabupaten Batang - Sapto Setyo Nugroho; Muhammad Adnan . (Journal of Politic and Government Studies, 2017)
One of the policies in the concept of good governance relating to the prevention of corruption is the Budget Transparency. Batang Regency Government is one example of the local governments that implement this policy. It is important to know the perceptions of bureaucracy and stakeholders on the implementation of budget transparency in Batang Regency Government, perception is analyzed so that it can be evaluated for various parties, it was then the purpose of this study.With the quantitative approach which uses a questionnaire as a research tool, the research data is extracted from the sample of respondents consisting of 37 Public, 31 Private and 23 Society. Then the data was analyzed using SPSS Program. The results showed an average knowledge of respondens to access information and documents was less out due to involvement in the management of budget that is less active. With the average knowledge of the respondens believe is very important and a good rate on the implementation aspect of budget transparency. It thus also affect the respondens who ecxpressed very agree an very support of all the implications and the attitude of budget transparency in Batang Regency Government.Keywords : Perception, Budget Transparency, Batang Regency Goverment